1986
DOI: 10.1111/j.1600-0722.1986.tb01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope and electron microprobe study of reactions of stannous fluoride and stannous chloride with dental enamel

Abstract: Ellingsen JE: Scanning electron microseope and electron microprobe study of reactions of stannous fluoride and stannous chloride with denial enamel. Scand J Dent Res 1986; 94: 299-305.Abstract -Stannous fluoride but not stannous chloride has shown a caries inhibiting effect in animal studies. The eJOfecJ of aqtieous solutions of stannous fluoride and stannous chloride on dental enamel surfaces was investigated by scanning electron microscope and analytical electron microprobe. Some large globules and a condnuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The reaction products of SnF 2 and enamel are not fully determined, but X-ray analysis showed that the aqueous reaction of SnF 2 and hydroxyapatite could result in the precipitation of Sn 2 OHPO 4 , Sn 3 F 3 PO 4 , Ca(SnF 3 ) 2 or CaF 2 salts [Babcock et al, 1978]. It has further been demonstrated that not only SnF 2 but also SnCl 2 is capable of depositing appreciable amounts of tin on enamel which were relatively stable in distilled water for days [Ellingsen, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction products of SnF 2 and enamel are not fully determined, but X-ray analysis showed that the aqueous reaction of SnF 2 and hydroxyapatite could result in the precipitation of Sn 2 OHPO 4 , Sn 3 F 3 PO 4 , Ca(SnF 3 ) 2 or CaF 2 salts [Babcock et al, 1978]. It has further been demonstrated that not only SnF 2 but also SnCl 2 is capable of depositing appreciable amounts of tin on enamel which were relatively stable in distilled water for days [Ellingsen, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…An early experiment [38] investigated the effects of Sn (as SnCl 2 ), on etched enamel. A 0.2% SnCl 2 solution was applied for 6 × 2 min and washed in between with running distilled water for 30 s after each treatment.…”
Section: Mechanisms Of Mineral Repair/precipitationmentioning
confidence: 99%
“…3 Stannous fluoride (SnF 2 ) solutions can form a surface glaze or coating when applied to enamel, which could have resulted in reduced enamel loss in various erosion only models. [4][5][6] Despite high concentrations of an aqueous NaF solution being shown to reduce erosion-attrition in vitro, 7 there are relatively few studies into the ability of NaF or SnF 2 aqueous fluoride solutions to withstand a combined erosive-abrasive challenge. Fluoride induced surface effects may remain on enamel for up to 12 weeks in vivo 8 and in vitro studies of NaF containing oral care products have been shown to offer protection from erosive drinks.…”
Section: Introductionmentioning
confidence: 99%